Analysis of factors influencing poverty in special region of Yogyakarta - Ayuandina, Fauzia Githa; El Hasanah, Lak lak Nazhat (Nur Science Institute, 2023)
This study examined how the poverty rate in Yogyakarta Special Region was affected simultaneously and partly by infrastructure, investments, economic growth, and district or city minimum salaries. In addition to time series data from 2014 to 2020, it used panel data with cross-sectional data from five districts or cities in the province of Yogyakarta Special Region. The Fixed Effect Model was the model employed in this investigation. The findings indicate that all independent variables, namely infrastructure, investment, economic growth, and district- or city-level minimum wages, affect the poverty rate simultaneously in the Special Region of Yogyakarta. The partial test results indicate that the infrastructure and investment variables have a positive but insignificant effect because they have yet to reach the periphery. In contrast, the economic growth variable has a significant impact.